Modular synthesis of self-assembling Janus-dendrimers and facile preparation of drug-loaded dendrimersomes. Issue 21 (17th May 2017) - Nummelin, Sami; Selin, Markus; Legrand, Sacha; Ropponen, Jarmo; Seitsonen, Jani; Nykänen, Antti; Koivisto, Jari; Hirvonen, Jouni; Kostiainen, Mauri A.; Bimbo, Luis M.
Abstract : A modular synthetic route for obtaining amphiphilic Janus-dendrimers and a one-step fabrication procedure for drug-loaded dendrimersomes. Abstract : Materials and methods aimed at the next generation of nanoscale carriers for drugs and other therapeutics are currently in great demand. Yet, creating these precise molecular arrangements in a feasible and straightforward manner represents a remarkable challenge. Herein we report a modular synthetic route for amphiphilic Janus-dendrimers via a copper-catalyzed click reaction (CuAAC) and a facile procedure, using simple injection, to obtain highly uniform dendrimersomes with efficient loading of the model drug compound propranolol. The resulting assemblies were analyzed by dynamic light scattering and cryogenic transmission electron microscopy revealing the formation of unilamellar and multilamellar dendrimersomes. The formation of a bilayer structure was confirmed using cryo-TEM and confocal microscopy visualization of an encapsulated solvatochromic dye (Nile Red). The dendrimersomes reported here are tunable in size, stable over time and display robust thermal stability in aqueous media. Our results expand the scope of dendrimer-based supramolecular colloidal systems and offer the means for one-step fabrication of drug-loaded dendrimersomes in the size range of 90–200 nm, ideal for biomedical applications.